Glycolytic Activation of CD14+ Intestinal Macrophages Contributes to the Inflammatory Responses via Exosomal Membrane Tumor Necrosis Factor in Crohn’s Disease - Zeng, Ziwei; Cheng, Sijing; Li, Xuanna; Liu, Huashan; Lin, Jinxin; Liang, Zhenxing; Liu, Xuanhui; Cao, Chao; Li, Shujuan; He, Xiaowen; Kang, Liang; Wu, Xiaojian; et al. (Inflammatory bowel diseases, 2024)
Abstract Background Macrophage (Mφ) activation plays a critical role in the inflammatory response. Activated Mφ go through profound reprogramming of cellular metabolism. However, changes in their intracellular energy metabolism and its effect on inflammatory responses in Crohn’s disease (CD) remain currently unclear. The aim of this study is to explore metabolic signatures of CD14+ Mφ and their potential role in CD pathogenesis as well as the underlying mechanisms. Methods CD14+ Mφ were isolated from peripheral blood or intestinal tissues of CD patients and control subjects. Real-time flux measurements and enzyme-linked immunosorbent assay were used to determine the inflammatory states of Mφ and metabolic signatures. Multiple metabolic routes were suppressed to determine their relevance to cytokine production. Results Intestinal CD14+ Mφ in CD patients exhibited activated glycolysis compared with those in control patients. Specifically, macrophagic glycolysis in CD largely induced inflammatory cytokine release. The intestinal inflammatory microenvironment in CD elicited abnormal glycolysis in Mφ. Mechanistically, CD14+ Mφ derived exosomes expressed membrane tumor necrosis factor (TNF), which engaged TNFR2 and triggered glycolytic activation via TNF/nuclear factor κB autocrine and paracrine signaling. Importantly, clinically applicable anti-TNF antibodies effectively prevented exosomal membrane TNF–induced glycolytic activation in CD14+ Mφ. Conclusions CD14+ Mφ take part in CD pathogenesis by inducing glycolytic activation via membrane TNF–mediated exosomal autocrine and paracrine signaling. These results provide novel insights into pathogenesis of CD and enhance understanding of the mechanisms of anti-TNF agents.